Code Halos how the digital lives of people, things, and organizations are changing the rules of business : a playbook for managers - Frank, Malcolm; Roehrig, Paul; Pring, Benjamin (Wiley, 2014)
Harness "Code Halos" to gain competitive advantage in the digital era Amazon beating Borders, Netflix beating Blockbuster, Apple beating Kodak, and the rise of companies like Google, LinkedIn, and Pandora are not isolated or random events. Today's outliers in revenue growth and value creation are winning with a new set of rules. They are dominating by managing the information that surrounds people, organizations, processes, and products-what authors Malcolm Frank, Paul Roehrig, and Ben Pring call Code Halos. This is far beyond "Big Data" and analytics. Code Halos spark new commercial models that can dramatically flip market dominance from industry stalwarts to challengers. In this new book, the authors show leaders how digital innovators and traditional companies can build Code Halo solutions to drive success. The book: Examines the explosion of digital information that now surrounds us and describes the profound impact this is having on individuals, corporations, and societies; Shows how the Crossroads Model can help anticipate and navigate this market shift; Provides examples of traditional firms already harnessing the power of Code Halos including GE's "Brilliant Machines," Disney's theme park "Magic Band," and Allstate's mobile devices and analytics that transform auto insurance. With reasoned insight, new data, real-world cases, and practical guidance, Code Halos shows seasoned executives, entrepreneurs, students, line-of-business owners, and technology leaders how to master the new rules of the Code Halo economy